ANALISIS KELAYAKAN BISNIS PADA UMKM KOPI KAULE DARI ASPEK PENGAMBILAN KEPUTUSAN DAN MANAJEMEN TENAGA KERJA YANG DI NILAI - Bintang Jaya Aknis; Febri Ariyantiningsih; Ratna Lia Wati; Virgiawan Ramadhana Yonisaputra; Yuaidarni Hati Laia (Jurnal Mahasiswa Entrepreneurship (JME), 2025)
Decision-making is an important aspect in the sustainability and development of Micro, Small, and Medium Enterprises (MSMEs), including the Kaule Coffee MSME which operates in the field of mobile coffee sales with an innovative concept using electric carts and bicycles. This study aims to analyze the decision-making process applied to the Kopi Kaule MSME and its impact on team operations and performance. The research methods used were observation and interviews with the owner and employees of Kopi Kaule. The results showed that the decision-making process at Kopi Kaule remains owner-centered, with a democratic and participatory leadership style in several operational aspects, such as menu selection, work schedules, and promotional strategies. Employees are given space to express their opinions, but the final decision rests with the owner. This situation facilitates rapid decision-making, but also creates a high level of dependence on the owner and limits employee initiative. Therefore, strengthening the decision-making system is necessary through delegation of authority, clearer division of tasks, and increased communication and regular evaluation. With more structured decision-making management, Kopi Kaule MSME is expected to improve operational effectiveness, team independence, and sustainable business competitiveness.